Pengaruh Pertumbuhan Kredit terhadap Kinerja Keuangan Bank yang Terdaftar di Bursa Efek Indonesia 2019-2021 - Nurjanah, Ika Eli; Imronudin (SAFE-Network, 2023)
The macroeconomic situation greatly affects the performance of most industries including the banking sector. The covid-19 pandemic is very influential on banking performance because when the real sector experiences a decline, lending will also be affected. The decline in lending will ultimately reduce the financial performance of the banking industry. This study aims to analyse the effect of credit growth on bank financial performance. The population of this study are national banks listed on the IDX. The sampling technique used purposive sampling. Based on the criteria set, there were 23 banks that became the sample of this study. The observation period was carried out from 2019 to 2021. The collected data were analysed using multiple regression. The results of this study indicate that non-performing loans (NPL) have a negative and significant effect on return on assets (ROA). Capital adequacy ratio (CAR) and size variables partially have a positive and significant effect on ROA. However, two other variables namely Loan to deposit ratio (LDR) and loan growth have no significant effect on financial performance.